Antibacterial flaky silver-coated copper powder, preparation method thereof and antibacterial fabric

CN122252601BActive Publication Date: 2026-10-27HEFEI SUNRISE PIGMENTS
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610739944.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-05-27
Publication Date
2026-10-27
Estimated Expiration
2046-05-27

AI Technical Summary

Technical Problem

[0007]还有,在抗菌耐久性与耐候性方面,现有银包铜粉普遍存在耐硫化腐蚀性能不足的问题

Benefits of technology

(1)本发明无需用氯化亚锡等敏化活化操作,仅仅通过活化分散剂对片状铜粉表面进行分散并轻度腐蚀形成铜的新活性表面,使银离子均匀定向沉积到铜颗粒表面,形成致密银壳层,并且铜粉和银壳层之间具有良好的接触和结合力,所得片状银包铜粉具有有效的抗菌防护性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122252601B_ABST
    Figure CN122252601B_ABST
Patent Text Reader

Abstract

The application provides antibacterial flaky silver-coated copper powder, a preparation method thereof and antibacterial fabric, and the preparation method comprises the following steps: mixing flaky copper powder with an alkaline solution to perform alkali washing to remove oil, to obtain pretreated copper powder; then, the pretreated copper powder is dissolved in water with an activation dispersant to perform activation and dispersion, to obtain an activated copper powder solution; a complexing agent is added into the activated copper powder solution, and the pH value is adjusted to weak alkalinity; then, a reducing agent solution and a silver-ammonia solution are added to perform a reduction reaction, to obtain flaky silver-coated copper powder; the flaky silver-coated copper powder is mixed with an aluminum source precursor to perform a gas phase chemical deposition reaction, to obtain flaky silver-coated copper powder with an alumina layer on the surface, i.e., the antibacterial flaky silver-coated copper powder; and the activation dispersant is obtained by addition reaction of polyvinylpyrrolidone and aminobenzenesulfonic acid. The antibacterial flaky silver-coated copper powder obtained by the application can completely replace pure silver material to some extent, can reduce the cost, and can effectively improve the antibacterial performance of the fabric after finishing modification.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of metal powder technology, and in particular to an antibacterial flake-shaped silver-coated copper powder, its preparation method, and an antibacterial fabric. Background Technology

[0002] With the improvement of people's living standards and the enhancement of health awareness, people are paying increasing attention to the impact of bacteria and other microorganisms on human health. As one of the consumer products that comes into closest contact with the human body daily, the antibacterial properties of textile products are directly related to the health and safety of users. Therefore, the rational selection of antibacterial textile products is of great significance in reducing the risk of bacterial infection and safeguarding human health. Cotton fibers and their products, as the main body of everyday textiles, while possessing excellent properties such as good moisture absorption, breathability, softness, and comfort, are extremely prone to bacterial growth in humid environments and lack inherent antibacterial functions. Therefore, modifying or finishing cotton fiber products to enhance their antibacterial function, endowing them with long-lasting and highly effective antibacterial properties, has become an important development direction for the textile industry.

[0003] Currently, commonly used inorganic antibacterial materials mainly fall into three categories: silver-based, copper-based, and zinc-based. Studies have shown that silver-based materials are most effective in inhibiting bacteria, copper-based materials are more significant in inhibiting fungi, and zinc-based materials can inhibit both bacteria and fungi, often being used in combination with copper-based materials. Silver ions possess broad-spectrum antibacterial activity, with antibacterial mechanisms including binding to proteins on bacterial cell membranes leading to cell rupture, binding to microbial DNA to inhibit replication, and generating reactive oxygen species that damage cell structure. However, the high cost of pure silver materials limits their large-scale, universal application. Although copper ions also have strong antibacterial activity, inducing oxidative stress and damaging bacterial cell membranes, and copper materials are much cheaper than silver, pure copper powder is easily oxidized, forming a copper oxide insulating layer on its surface in humid environments, leading to a significant decrease in conductivity and antibacterial activity. Furthermore, the antibacterial effect of copper powder is relatively weak, making it difficult to achieve the ideal broad-spectrum antibacterial level.

[0004] To address the aforementioned issues, silver-coated copper powder materials have emerged. Silver-coated copper powder is a core-shell structured composite functional material with copper particles as the core and a dense silver layer uniformly coated on the surface. It has broad application prospects in textile antibacterial applications, conductive fillers, electromagnetic shielding, photovoltaic electronic pastes, and catalysis. Through the core-shell structure design of "replacing silver with copper," silver-coated copper powder can significantly reduce production costs while maintaining the excellent antibacterial activity and conductivity of silver powder. Furthermore, it overcomes the oxidation defects of pure copper powder and solves the limitation of the high price of pure silver powder, making it a high-performance composite functional material with excellent cost-effectiveness.

[0005] However, existing silver-coated copper powder technologies still face numerous technical bottlenecks when applied to the field of textile antibacterial applications: Firstly, regarding the preparation process, current methods for preparing silver-coated copper powder mainly include mechanical ball milling, melt spraying, and electroless plating, among which electroless plating (including displacement and reduction methods) is the most important and economical method. However, silver-coated copper powder prepared by chemical displacement often suffers from thin and porous coatings. The rapid displacement reaction makes it difficult for the silver coating to uniformly and densely encapsulate the copper core. While chemical reduction combines displacement and reduction processes, the plating solution has complex composition and its stability is difficult to guarantee. Furthermore, the multiple electroless plating processes are cumbersome and costly. Silver-coated copper powder prepared by existing technologies generally suffers from uneven coating and low density. Pores and defects easily appear on the surface of the silver layer, causing the internal copper core to be easily exposed to the environment during subsequent processing or use.

[0006] Secondly, regarding the bonding strength at the silver-copper interface, in existing silver-coated copper powders, the thin silver layer is prone to detachment under mechanical stress during slurry rolling or textile finishing processes, exposing the copper core and causing a sharp decline in the material's oxidation resistance and antibacterial properties. Insufficient bonding strength between the silver layer and the copper core is a key technical challenge restricting the widespread application of silver-coated copper powder in high-end fields.

[0007] Furthermore, existing silver-coated copper powders generally suffer from insufficient resistance to sulfide corrosion in terms of antibacterial durability and weather resistance. Sweat and secretions produced during normal human physiological activities contain sulfides. These sulfides react with the silver layer to form black silver sulfide, which not only affects the product's appearance but also significantly reduces or even eliminates the antibacterial activity of the silver layer. Simultaneously, typical silver-coated copper powders begin to oxidize at around 150-230℃, exhibiting poor corrosion resistance. In addition, the copper exposed on the surface easily oxidizes to form a CuO insulating layer, leading to a sharp drop in conductivity (approximately 90% conductivity loss). These factors severely restrict the long-term stability of silver-coated copper powders in antibacterial textiles.

[0008] In conclusion, developing a silver-coated copper powder that combines strong antibacterial properties, low production cost, dense silver coating, strong silver-copper interface bonding, and excellent resistance to sulfide corrosion is of great significance for promoting the industrial upgrading of antibacterial textile products. Summary of the Invention

[0009] Based on the technical problems existing in the background art, the present invention proposes an antibacterial flake silver-coated copper powder, its preparation method, and an antibacterial fabric. By coating the surface of the flake copper powder with a silver shell layer and simultaneously depositing an alumina protective layer, on the one hand, the silver shell layer formed on the surface of the flake copper powder after dispersion and activation treatment is uniform and dense, with strong interfacial bonding, resistance to oxidation and corrosion, and strong antibacterial durability. On the other hand, the alumina protective layer formed by vapor deposition aims to improve the antioxidant properties of the silver-coated copper powder in the human body fluid environment. The resulting antibacterial flake silver-coated copper powder can completely replace pure silver materials to a certain extent, reducing costs while effectively improving its antibacterial performance after being used for fabric finishing and modification.

[0010] The present invention proposes a method for preparing antibacterial flake-shaped silver-coated copper powder, comprising the following steps: S1. Mix the flake copper powder with an alkaline solution and perform alkaline washing to remove oil, then dissolve the pretreated copper powder and an activating dispersant in water to activate and disperse, thus obtaining an activated copper powder solution. S2. Add a complexing agent to the activated copper powder solution and adjust the pH to weakly alkaline. Then add a reducing agent solution and silver ammonia solution to carry out a reduction reaction to obtain flake-shaped silver-coated copper powder. S3. After mixing the flake-shaped silver-coated copper powder with the aluminum source precursor and performing a vapor phase chemical deposition reaction, flake-shaped silver-coated copper powder with an aluminum oxide layer on the surface is obtained, which is the antibacterial flake-shaped silver-coated copper powder. In step S2, the activating dispersant is obtained by an addition reaction of polyvinylpyrrolidone and aminobenzenesulfonic acid.

[0011] In this invention, organic matter, grease, and oxide layers on the surface of flake copper powder are first removed by alkaline washing. Then, the alkaline-washed flake copper powder is mixed with an activating dispersant. On the one hand, the polyvinylpyrrolidone fragments on the activating dispersant disperse the copper particles, which act as a steric barrier to resist the attraction between particles, keeping them in suspension and preventing agglomeration. On the other hand, the sulfonic acid fragments on the activating dispersant perform mild corrosion to form a new active surface for copper, which helps silver ions to be directionally deposited on the copper surface to form a dense silver shell layer. Finally, chemical silver plating is performed so that the silver layer can effectively coat the surface of the copper powder, enhancing the interfacial bonding strength between the silver and copper layers and significantly improving the density and uniformity of the silver plating layer. At the same time, in addition to preparing silver-coated copper powder using liquid-phase chemical deposition, this invention also uses gas-phase chemical deposition to deposit an alumina protective layer on the surface of the silver-coated copper powder, thereby constructing an effective antioxidant barrier and improving the antioxidant properties of the obtained silver-coated copper powder in the human body fluid environment, enabling it to be effectively applied to antibacterial fabrics.

[0012] Preferably, in step S1, the alkaline solution is at least one of sodium hydroxide, soda ash, sodium silicate, or sodium tripolyphosphate solution; The alkaline washing and degreasing process takes place at a temperature of 10-30℃ for 0.5-2 hours.

[0013] Preferably, in step S1, the structure of the activating dispersant is illustrated below: where n is the degree of aggregation; The mass ratio of the flaky copper powder to the activating dispersant is 1:0.01-0.1; The activation and dispersion are carried out at a temperature of 30-50℃ for 1-3 hours.

[0014] In this invention, compared to simply adding polyvinylpyrrolidone and aminobenzenesulfonic acid as dispersants and activators, although they can disperse or remove oxides on the surface of copper powder to a certain extent, they cannot effectively attach the activating dispersant to the surface of the dispersed copper powder particles, thus promoting the directional and uniform deposition of silver ions onto the copper surface, thereby obtaining an ideal silver film composed of uniformly distributed, tightly bound silver particles with a pore-free and highly dense surface.

[0015] Preferably, in step S2, the complexing agent is at least one of disodium ethylenediaminetetraacetate, ethylenediaminetetraacetic acid, thiourea, thioaminourea, sodium thiosulfate, or ethylenediamine. The mass ratio of the flaky copper powder to the complexing agent is 1:0.1-0.5.

[0016] In this invention, the complexing agent complexes silver ions, which gradually dissolve and are reduced to the surface of copper powder according to the principle of equilibrium concentration. This can inhibit the supersaturation and self-nucleation growth process of silver ions under reducing conditions.

[0017] Preferably, in step S2, the reducing agent solution is at least one of glucose, ascorbic acid, tartaric acid, citric acid, L-histidine, glutamic acid, formaldehyde, acetaldehyde, sodium borohydride, or triethanolamine solution. The mass ratio of the reducing agent in the flaky copper powder and reducing agent solution is 1:0.01-5, preferably 1:0.05-0.5; the mass ratio of silver nitrate in the flaky copper powder and silver ammonia solution is 1:0.01-1, preferably 1:0.05-0.15. The reduction reaction is carried out at a temperature of 20-60℃ for 1-3 hours.

[0018] Preferably, in step S3, the aluminum source precursor is at least one of aluminum acetylacetonate, triethylaluminum, or triisobutylaluminum; The temperature of the vapor phase chemical deposition reaction is 200-250℃, and the time is 0.5-2h.

[0019] In this invention, the deposition and coating of alumina can also fill the pores and non-dense sites on the silver coating layer. According to the theory of metal nucleation and growth, the above-mentioned sites have crystal defects, and new phases tend to nucleate and grow here. In this way, a dense coating can be achieved on the copper substrate and the silver coating layer can play an antibacterial role. In the specific vapor-phase chemical deposition process, an alumina protective layer is constructed on the surface of the flake-shaped silver-coated copper powder particles. This process uses aluminum acetylacetonate and other safe aluminum sources, and is carried out under inert gas protection throughout. The core reaction temperature is controlled at 250℃ or below, avoiding the high-temperature densification step, making it suitable for surface modification of heat-sensitive substrate materials. The following is a detailed process flow and technical description in stages: Phase 1: Reaction System Setup and Substrate Pretreatment Charging and Inert Atmosphere Construction: Silver-coated copper powder is first loaded into a heatable reactor (such as a fluidized bed or fixed bed reactor), and then high-purity argon (or nitrogen) is introduced into the reactor at a stable flow rate of 1-2 L / min. The core purpose is to completely replace the air in the reactor and eliminate oxygen and water vapor. The continuous introduction creates a slight positive pressure inside the reactor, effectively preventing outside air from seeping in during subsequent steps, and creating an oxygen-free and water-free "safe inert chamber" for the entire reaction. Temperature program and surface activation: Under the condition of maintaining an inert gas flow (1-2 L / min), start the heating program; raise the temperature of the reaction system to 150-200℃ at a relatively slow rate of 5-10℃ / min, and hold at this temperature for 10-30 min; this step has multiple purposes: firstly, to disperse the water molecules and gases physically adsorbed on the surface of the silver-coated copper powder by gentle heating; secondly, to make the powder particles temperature uniform and reduce the thermal stress during subsequent deposition; thirdly, a certain degree of preheating can "activate" the powder surface, which may expose more active sites, which is beneficial to the subsequent chemical adsorption and film formation of precursors; Phase 2: Precursor transport and surface deposition reaction (core step) Stable reaction temperature: The reactor temperature is precisely stabilized within a window of 200-250℃; this temperature range is the starting range for the effective thermal decomposition of aluminum acetylacetonate, which can ensure that it decomposes to produce active aluminum species, while avoiding oxidation, sintering or grain growth of the silver-coated copper powder substrate due to excessive temperature. Aluminum source introduction and parameter control: The aluminum source is delivered by solution atomization, which is the key design of this process. Solid aluminum acetylacetonate is dissolved in a low-boiling-point alcohol solvent (such as isopropanol) to prepare a homogeneous solution with a concentration of 0.05-0.2 mol / L. The solution is injected into the atomizer at a low speed of 0.1-0.5 mL / min through a precision metering pump. At the same time, an argon gas (atomizing carrier gas) with a flow rate of 0.5-1.5 L / min atomizes the solution into micron-sized droplets and carries them into the thermal reaction zone. Surface reaction and film growth: After the atomized droplets enter the hot zone of 200-250℃, the solvent evaporates instantly, and the aluminum acetylacetonate vapor comes into contact with the surface of the incandescent silver-coated copper powder. At this temperature, aluminum acetylacetonate molecules generate aluminum oxide or its precursor species through thermal decomposition reaction (possibly undergoing ligand release, oxidation, etc.), and are deposited layer by layer on the powder surface. This deposition process lasts for 30-120 minutes. By controlling the reaction time and the precursor feed rate, the thickness and coverage of the coating layer can be initially controlled. The deposition process is carried out in a continuous inert atmosphere to prevent the oxidation of the active intermediates. Phase 3: Reaction Termination, Purification, and Post-treatment System purging and cooling: After the predetermined reaction time is reached, stop the delivery of the precursor solution, but continue to purge the reactor with an argon flow rate of 1-2 L / min for at least 30 min. This is to thoroughly remove unreacted precursors and decomposition byproducts (such as organic matter such as acetylacetone) remaining in the reaction chamber and between the powders. Then, under argon protection, allow the reaction system to cool to room temperature naturally or through a program to ensure that the product is not oxidized during the cooling process. Controlled passivation treatment: To obtain chemically stable products with long-term preservation properties, the active aluminum species on the surface of the deposited powder need to be passivated. The cooled powder is slowly exposed to a controlled, low-concentration oxygen atmosphere (e.g., a gas composed of 1-5% oxygen mixed with nitrogen or argon) for 1-12 hours. This process allows oxygen to react gently with the outermost active aluminum to form a dense, stable stoichiometric alumina (Al2O3) passivation film, thereby "sealing" and enhancing the environmental stability of the entire coating layer.

[0020] Preferably, the method further includes step S4, adding an aminosilane coupling agent solution to the flake silver-coated copper powder with an alumina coating to carry out a hydrolysis reaction, and then adding aldehyde-based polyethylene glycol to carry out an addition reaction to obtain hydrophilic modified flake silver-coated copper powder.

[0021] Preferably, the aminosilane coupling agent is at least one selected from 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-aminoethyl-3-aminopropyltrimethoxysilane, or N-aminoethyl-3-aminopropyltriethoxysilane. The mass ratio of the sheet-like silver-coated copper powder with an alumina coating, the aminosilane coupling agent, and the aldehyde-based polyethylene glycol is 1:0.01-0.1:0.05-0.2.

[0022] In this invention, flake-shaped silver-coated copper powder with an alumina layer on its surface is modified by coupling with an aminosilane coupling agent, thereby grafting amino active sites onto its surface. Then, it is added with a hydrophilic polymer of aldehyde-based polyethylene glycol, so that the hydrophilic polymer is firmly bound to the surface of the silver-coated copper powder, improving the affinity of the silver-coated copper powder to cotton fabrics and ensuring that the adhesion of the silver-coated copper powder to cotton fabrics is enhanced, thus maintaining its antibacterial ability for a longer period of time.

[0023] The present invention also proposes an antibacterial flake-shaped silver-coated copper powder, which is prepared by the above preparation method.

[0024] The present invention also proposes an antibacterial fabric, which includes a cotton fabric and the aforementioned antibacterial flake-shaped silver-coated copper powder loaded on the surface of the cotton fabric.

[0025] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) This invention does not require sensitization and activation operations such as stannous chloride. It simply disperses the surface of the flake copper powder with an activating dispersant and lightly corrodes it to form a new active surface of copper, so that silver ions are uniformly and oriented to be deposited on the surface of copper particles to form a dense silver shell layer. Furthermore, there is good contact and bonding between the copper powder and the silver shell layer. The resulting flake silver-coated copper powder has effective antibacterial protective properties.

[0026] (2) The present invention also forms a uniform aluminum oxide coating layer on the surface of the flake silver-coated copper powder, thereby constructing an effective antioxidant barrier, and finally forming a highly stable and affordable antibacterial flake silver-coated copper, which is more suitable for long-term antibacterial application on cotton fabrics. Attached Figure Description

[0027] Figure 1 The infrared spectrum of the activating dispersant described in Example 1 of this invention; Figure 2 This is a scanning electron microscope image of the antibacterial flake-shaped silver-coated copper powder described in Example 1 of the present invention. Detailed Implementation

[0028] The technical solution of the present invention will be described in detail below through specific embodiments. However, it should be clearly stated that these embodiments are for illustrative purposes only and are not intended to limit the scope of the present invention.

[0029] Example 1 An antibacterial flake-shaped silver-coated copper powder, the preparation method of which includes: (1) Add flake copper powder (1000-3000 mesh) to a 10 g / L sodium hydroxide solution. The mass ratio of flake copper powder to sodium hydroxide solution is 1:30. Stir continuously at room temperature for 1 h, then filter, wash with deionized water until neutral, and dry to obtain pretreated copper powder. Add the pretreated copper powder to deionized water, stir at room temperature for 10 min, and then add an activating dispersant. The mass ratio of flake copper powder, deionized water and activating dispersant is 1:20:0.05. Stir and disperse in a 40℃ water bath for 2 h to obtain an activated copper powder solution. The activated dispersant is prepared by the following method: polyvinylpyrrolidone (K30) is dissolved in anhydrous ethanol, p-aminobenzenesulfonic acid is added, the mass ratio of polyvinylpyrrolidone to p-aminobenzenesulfonic acid is 1:0.05, the mixture is heated under reflux for 3 hours, the ethanol is removed by rotary evaporation, the mixture is dissolved in chloroform and washed twice with water, and the mixture is concentrated under reduced pressure to obtain the activated dispersant. (2) Add disodium ethylenediaminetetraacetate to the activated copper powder solution. The mass ratio of flake copper powder to disodium ethylenediaminetetraacetate is 1:0.3. After stirring continuously for 10 min, add sodium hydroxide solution to adjust the pH to 11-12. Then add an aqueous solution containing 100 g / L potassium sodium tartrate and 50 g / L glucose. The mass ratio of flake copper powder to potassium sodium tartrate is 1:0.2. After stirring continuously for 20 min, slowly add silver ammonia solution. The silver ammonia solution is obtained by adding 28 wt% ammonia water dropwise to 50 g / L silver nitrate solution until the precipitate disappears. The mass ratio of flake copper powder to silver nitrate is 1:0.1. After the addition is complete, stir continuously in a 30°C water bath for 2 h. After centrifugation, wash with deionized water until neutral, wash twice with ethanol, and vacuum dry to obtain flake silver-coated copper powder. (3) The flake-shaped silver-coated copper powder is loaded into a fluidized bed reactor, and argon gas with a flow rate of 1.5 L / min is introduced to replace the air in the fluidized bed reactor. The temperature is then raised to 250°C at a heating rate of 10°C / min and held for 20 min. Then, 0.1 mol / L aluminum acetylacetonate in isopropanol solution is injected into the atomizer at a low speed of 0.3 mL / min. At the same time, argon gas with a flow rate of 1 L / min is used to atomize the solution into micron-sized droplets and then introduce them into the fluidized bed reactor for gas phase chemical deposition reaction. After 60 min, the supply of atomizing liquid is stopped, and argon gas with a flow rate of 1.5 L / min is continuously introduced for 30 min. The reactor is cooled to room temperature and then exposed in a mixture of oxygen and nitrogen with an oxygen volume fraction of 3% for 6 h to obtain flake-shaped silver-coated copper powder with an alumina layer on the surface, which is the antibacterial flake-shaped silver-coated copper powder.

[0030] Figure 1 The infrared spectrum of the activating dispersant described in this embodiment is shown below. Figure 1 As shown, 3010-2900cm -1 The peak at 1656 cm⁻¹ represents the stretching vibration peak of CH on the benzene ring and the stretching vibration peak of -CH₂- on pyrrole. -1 The peak of the stretching vibration at C=N is 1463 cm⁻¹. -1 The peak at 624 cm⁻¹ represents the stretching vibration of CN on pyrrole. -1 The peak at this location is the bent absorption peak of -SO3H.

[0031] Figure 2 This is a scanning electron microscope image of the antibacterial flake-shaped silver-coated copper powder described in this embodiment, as shown below. Figure 2 As shown, the silver-coated copper powder has a sheet-like structure with a coating layer on its surface.

[0032] Example 2 An antibacterial flake-shaped silver-coated copper powder, the preparation method of which includes: (1) Add flake copper powder (1000-3000 mesh) to an alkaline solution containing 15 g / L soda ash and 5 g / L sodium hydroxide. The mass ratio of flake copper powder to sodium hydroxide solution is 1:30. After stirring continuously at room temperature for 0.5 h, filter, wash with deionized water until neutral, and dry to obtain pretreated copper powder. Add the pretreated copper powder to deionized water, stir at room temperature for 10 min, and then add an activating dispersant. The mass ratio of flake copper powder, deionized water and activating dispersant is 1:20:0.1. Stir and disperse in a 30℃ water bath for 3 h to obtain an activated copper powder solution. The activated dispersant is prepared by the following method: polyvinylpyrrolidone (K30) is dissolved in anhydrous ethanol, m-aminobenzenesulfonic acid is added, the mass ratio of polyvinylpyrrolidone to m-aminobenzenesulfonic acid is 1:0.05, the mixture is heated under reflux for 3 hours, the ethanol is removed by rotary evaporation, the mixture is dissolved in chloroform and washed twice with water, and the mixture is concentrated under reduced pressure to obtain the activated dispersant. (2) Add ethylenediaminetetraacetic acid to the activated copper powder solution. The mass ratio of flaky copper powder to ethylenediaminetetraacetic acid is 1:0.1. After stirring continuously for 10 min, add sodium hydroxide solution to adjust the pH to 11-12. Then add an aqueous solution containing 50 g / L ascorbic acid and 50 g / L L-histidine. The mass ratio of flaky copper powder to ascorbic acid is 1:0.25. After stirring continuously for 20 min, slowly add silver ammonia solution. The silver ammonia solution is obtained by adding 28 wt% ammonia water dropwise to 50 g / L silver nitrate solution until the precipitate disappears. The mass ratio of flaky copper powder to silver nitrate is 1:0.1. After the addition is complete, stir continuously in a 60℃ water bath for 3 h. After centrifugation, wash with deionized water until neutral, wash twice with ethanol, and vacuum dry to obtain flaky silver-coated copper powder. (3) The flake-shaped silver-coated copper powder is loaded into a fluidized bed reactor, and argon gas with a flow rate of 1 L / min is introduced to replace the air in the fluidized bed reactor. The temperature is then raised to 200℃ at a heating rate of 5℃ / min and held for 30 min. Then, 0.2 mol / L aluminum acetylacetonate in isopropanol solution is injected into the atomizer at a low speed of 0.1 mL / min. At the same time, argon gas with a flow rate of 0.5 L / min atomizes the solution into micron-sized droplets and introduces them into the fluidized bed reactor for gas phase chemical deposition reaction. After 30 min, the supply of atomizing liquid is stopped, and argon gas with a flow rate of 1 L / min is continuously introduced for 30 min. The reactor is cooled to room temperature and then exposed in a mixed gas of oxygen and nitrogen with an oxygen volume fraction of 1% for 12 h to obtain flake-shaped silver-coated copper powder with an alumina layer on the surface, which is the antibacterial flake-shaped silver-coated copper powder.

[0033] Example 3 An antibacterial flake-shaped silver-coated copper powder, the preparation method of which includes: (1) Add flake copper powder (1000-3000 mesh) to a 10 g / L sodium hydroxide solution. The mass ratio of flake copper powder to sodium hydroxide solution is 1:30. Stir continuously at room temperature for 2 hours, then filter, wash with deionized water until neutral, and dry to obtain pretreated copper powder. Add the pretreated copper powder to deionized water, stir at room temperature for 10 minutes, and then add an activating dispersant. The mass ratio of flake copper powder, deionized water and activating dispersant is 1:20:0.01. Stir and disperse in a 50°C water bath for 1 hour to obtain an activated copper powder solution. The activating dispersant was prepared according to the preparation method described in Example 1; (2) Sodium thiosulfate was added to the activated copper powder solution. The mass ratio of flake copper powder to sodium thiosulfate was 1:0.5. After stirring continuously for 10 min, sodium hydroxide solution was added to adjust the pH to 11-12. Then, 50 g / L sodium borohydride aqueous solution was added. The mass ratio of flake copper powder to sodium borohydride was 1:0.05. After stirring continuously for 20 min, silver ammonia solution was slowly added. The silver ammonia solution was obtained by adding 28 wt% ammonia water dropwise to 50 g / L silver nitrate solution until the precipitate disappeared. The mass ratio of flake copper powder to silver nitrate was 1:0.1. After the addition was completed, the reaction was stirred continuously in a 20°C water bath for 1 h. After centrifugation, the mixture was washed with deionized water until neutral, washed twice with ethanol, and dried under vacuum to obtain flake silver-coated copper powder. (3) The flake-shaped silver-coated copper powder is loaded into a fluidized bed reactor, and argon gas with a flow rate of 2L / min is introduced to replace the air in the fluidized bed reactor. The temperature is then raised to 250℃ at a heating rate of 10℃ / min and held for 10min. Then, 0.05mol / L aluminum acetylacetonate in isopropanol solution is injected into the atomizer at a low speed of 0.5mL / min. At the same time, argon gas with a flow rate of 1.5L / min atomizes the solution into micron-sized droplets and introduces them into the fluidized bed reactor for gas phase chemical deposition reaction. After 120min, the supply of atomizing liquid is stopped, and argon gas with a flow rate of 2L / min is continuously introduced for 30min. The reactor is cooled to room temperature and then exposed in a mixture of oxygen and nitrogen with an oxygen volume fraction of 5% for 1h to obtain flake-shaped silver-coated copper powder with an alumina layer on the surface, which is the antibacterial flake-shaped silver-coated copper powder.

[0034] Example 4 An antibacterial flake-shaped silver-coated copper powder, the preparation method of which includes: (1) Add flake copper powder (1000-3000 mesh) to a 10 g / L sodium hydroxide solution. The mass ratio of flake copper powder to sodium hydroxide solution is 1:30. Stir continuously at room temperature for 1 h, then filter, wash with deionized water until neutral, and dry to obtain pretreated copper powder. Add the pretreated copper powder to deionized water, stir at room temperature for 10 min, and then add an activating dispersant. The mass ratio of flake copper powder, deionized water and activating dispersant is 1:20:0.05. Stir and disperse in a 40℃ water bath for 2 h to obtain an activated copper powder solution. The activating dispersant was prepared according to the preparation method described in Example 1; (2) Add disodium ethylenediaminetetraacetate to the activated copper powder solution. The mass ratio of flake copper powder to disodium ethylenediaminetetraacetate is 1:0.3. After stirring continuously for 10 min, add sodium hydroxide solution to adjust the pH to 11-12. Then add an aqueous solution containing 100 g / L potassium sodium tartrate and 50 g / L glucose. The mass ratio of flake copper powder to potassium sodium tartrate is 1:0.2. After stirring continuously for 20 min, slowly add silver ammonia solution. The silver ammonia solution is obtained by adding 28 wt% ammonia water dropwise to 50 g / L silver nitrate solution until the precipitate disappears. The mass ratio of flake copper powder to silver nitrate is 1:0.1. After the addition is complete, stir continuously in a 30°C water bath for 2 h. After centrifugation, wash with deionized water until neutral, wash twice with ethanol, and vacuum dry to obtain flake silver-coated copper powder. (3) The flake-shaped silver-coated copper powder is loaded into a fluidized bed reactor, and argon gas with a flow rate of 1.5 L / min is introduced to replace the air in the fluidized bed reactor. The temperature is then raised to 250°C at a heating rate of 10°C / min and held for 20 min. Then, 0.1 mol / L aluminum acetylacetonate in isopropanol solution is injected into the atomizer at a low speed of 0.3 mL / min. At the same time, argon gas with a flow rate of 1 L / min is used to atomize the solution into micron-sized droplets and then introduce it into the fluidized bed reactor for gas phase chemical deposition reaction. After 60 min, the supply of atomizing liquid is stopped, and argon gas with a flow rate of 1.5 L / min is continuously introduced for 30 min. The reactor is cooled to room temperature and then exposed in a mixture of oxygen and nitrogen with an oxygen volume fraction of 3% for 6 h to obtain flake-shaped silver-coated copper powder with an alumina layer on the surface. (4) The flake-shaped silver-coated copper powder with an alumina coating is mixed with isopropanol at a mass ratio of 1:10. After heating to 50°C, an isopropanol solution containing 3-aminopropyltrimethoxysilane is added dropwise, and a mixed solution of water and ethylenediamine at a mass ratio of 1:1.5 is added dropwise. After stirring continuously for 2 hours, dialdehyde polyethylene glycol (the number average molecular weight of polyethylene glycol segments is 600) is added. The mass ratio of the flake-shaped silver-coated copper powder with an alumina coating, 3-aminopropyltrimethoxysilane, ethylenediamine and dialdehyde polyethylene glycol is 1:0.05:0.01:0.1. The mixture is stirred continuously at 70°C for 3 hours, centrifuged, washed three times with ethanol, and vacuum dried to obtain hydrophilic modified silver-coated copper powder, which is the antibacterial flake-shaped silver-coated copper powder.

[0035] Comparative Example 1 An antibacterial flake-shaped silver-coated copper powder is prepared according to Example 1, except that in step (1), the pretreated copper powder is added to deionized water, stirred at room temperature for 10 min, and then added to polyvinylpyrrolidone (K30). The mass ratio of flake copper powder, deionized water and polyvinylpyrrolidone is 1:20:0.05. After stirring and dispersing in a water bath at 40°C for 2 h, an activated copper powder solution is obtained.

[0036] Comparative Example 2 An antibacterial flake-shaped silver-coated copper powder is prepared according to Example 1, except that in step (1), the pretreated copper powder is added to deionized water, stirred at room temperature for 10 min, and then p-aminobenzenesulfonic acid is added. The mass ratio of flake copper powder, deionized water and p-aminobenzenesulfonic acid is 1:20:0.05. After stirring and dispersing in a water bath at 40℃ for 2 h, an activated copper powder solution is obtained.

[0037] Comparative Example 3 An antibacterial flake-shaped silver-coated copper powder is prepared according to Example 1, except that in step (1), the pretreated copper powder is added to deionized water, stirred at room temperature for 10 min, and then polyvinylpyrrolidone and p-aminobenzenesulfonic acid are added. The mass ratio of flake copper powder, deionized water, polyvinylpyrrolidone and p-aminobenzenesulfonic acid is 1:20:0.045:0.005. After stirring and dispersing in a water bath at 40°C for 2 h, an activated copper powder solution is obtained.

[0038] Comparative Example 4 An antibacterial flake-shaped silver-coated copper powder is prepared according to Example 4, except that in step (4), the flake-shaped silver-coated copper powder with an alumina coating is mixed with isopropanol at a mass ratio of 1:10, heated to 50°C, and then an isopropanol solution containing 3-aminopropyltrimethoxysilane is added dropwise. At the same time, a mixed solution of water and ethylenediamine at a mass ratio of 1:1.5 is added dropwise. The mass ratio of the flake-shaped silver-coated copper powder with an alumina coating, 3-aminopropyltrimethoxysilane and ethylenediamine is 1:0.1:0.02. After stirring continuously for 2 hours, the mixture is centrifuged, washed three times with ethanol, and vacuum dried to obtain hydrophilic modified silver-coated copper powder, which is the antibacterial flake-shaped silver-coated copper powder.

[0039] Application examples An antibacterial fabric, the preparation method of which includes: (1) Add 2.5 parts by weight of the antibacterial flake-shaped copper-coated powder described in the above example or comparative example, 2.5 parts by weight of waterborne polyurethane and 0.1 parts by weight of sodium polyacrylate to 28 parts by weight of water, stir continuously at room temperature for 10 min, and then ultrasonically disperse for 30 min to obtain a flake-shaped copper-coated powder dispersion solution. (2) Two parts by weight of cotton fabric are immersed in the above-mentioned flake silver-coated copper powder dispersion solution. After immersion for 20 minutes, the immersed fabric is treated with a rolling mill to remove excess water. The fabric is immersed and rolled twice, maintaining a roll rate of 80%. After finishing, it is pre-dried at 60°C for 10 minutes, rinsed three times with warm water at 20°C, and then dried at 90°C for 10 minutes to obtain the antibacterial fabric.

[0040] The antibacterial effects of the antibacterial fabrics described in the examples and comparative examples were determined by the oscillation method specified in GB / T 20944.3-2008, and the results are shown in Table 1. Table 1. Test results of antimicrobial properties of the antimicrobial fabrics obtained in the examples and comparative examples.

[0041] As can be seen from Table 1, compared with pure silver powder, the antibacterial properties of the antibacterial flake silver-coated copper powder obtained by optimizing the silver coating layer in this invention are basically close; and compared with simply adding polyvinylpyrrolidone or aminobenzenesulfonic acid as a dispersant, the antibacterial flake silver-coated copper powder obtained by activating the flake copper powder deposition with an activating dispersant obtained by the addition reaction of polyvinylpyrrolidone and aminobenzenesulfonic acid has more effective antibacterial protective properties.

[0042] The abrasion resistance and antibacterial effect of the antibacterial fabrics described in the examples and comparative examples were determined according to the following methods, and the results are shown in Table 2. Friction test simulates wear and tear in daily wear: The antibacterial fabric sample was subjected to 1,000 reciprocating friction cycles with the abrasive under standard pressure using a Martindale abrasion tester. The amount of silver residue on the surface after friction was measured by X-ray fluorescence spectrometry, and its "adhesion retention rate" relative to the initial value was calculated. Ultrasonic treatment tests simulate and accelerate extreme mechanical actions (such as strong water flow impact): The antibacterial fabric sample is immersed in water and placed in an ultrasonic cleaner. The surface is continuously impacted by the intense "cavitation effect" generated by high-frequency vibration. After treatment for 30 minutes, the retention rate is calculated by measuring the amount of silver residue.

[0043] Table 2. Performance test results of the antimicrobial fabrics obtained in the examples and comparative examples.

[0044] As can be seen from Table 1, compared with pure silver powder, the present invention provides mechanical support through a copper substrate, which enhances the adhesion of the silver layer, and the aluminum oxide layer fixes the silver layer through chemical bonding, reducing peeling. The resulting antibacterial fabric has excellent adhesion.

[0045] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A method for preparing antibacterial flake-shaped silver-coated copper powder, characterized in that, Includes the following steps: S1. Mix the flake copper powder with an alkaline solution and perform alkaline washing to remove oil, then dissolve the pretreated copper powder and an activating dispersant in water to activate and disperse, thus obtaining an activated copper powder solution. S2. Add a complexing agent to the activated copper powder solution and adjust the pH to 11-12. Then add a reducing agent solution and silver ammonia solution to carry out a reduction reaction to obtain flake-shaped silver-coated copper powder. S3. After mixing the flake-shaped silver-coated copper powder with the aluminum source precursor and performing a vapor phase chemical deposition reaction, flake-shaped silver-coated copper powder with an aluminum oxide layer on the surface is obtained, which is the antibacterial flake-shaped silver-coated copper powder. In step S1, the activating dispersant is obtained by an addition reaction of polyvinylpyrrolidone and aminobenzenesulfonic acid; The structure of the activating dispersant is shown below. 。 2. The method for preparing antibacterial flake-shaped silver-coated copper powder according to claim 1, characterized in that, In step S1, the alkaline solution is at least one of sodium hydroxide, soda ash, sodium silicate, or sodium tripolyphosphate solution; The alkaline washing and degreasing process takes place at a temperature of 10-30℃ for 0.5-2 hours.

3. The method for preparing antibacterial flake-shaped silver-coated copper powder according to claim 1, characterized in that, In step S1, the mass ratio of the flake copper powder to the activating dispersant is 1:0.01-0.1; The activation and dispersion are carried out at a temperature of 30-50℃ for 1-3 hours.

4. The method for preparing antibacterial flake-shaped silver-coated copper powder according to any one of claims 1-3, characterized in that, In step S2, the complexing agent is at least one of disodium ethylenediaminetetraacetate, ethylenediaminetetraacetic acid, thiourea, thioaminourea, sodium thiosulfate, or ethylenediamine. The mass ratio of the flaky copper powder to the complexing agent is 1:0.1-0.

5.

5. The method for preparing antibacterial flake-shaped silver-coated copper powder according to any one of claims 1-3, characterized in that, In step S2, the reducing agent solution is at least one of glucose, ascorbic acid, tartaric acid, citric acid, L-histidine, glutamic acid, formaldehyde, acetaldehyde, sodium borohydride, or triethanolamine solution. The mass ratio of the reducing agent in the flaky copper powder and reducing agent solution is 1:0.01-5; the mass ratio of silver nitrate in the flaky copper powder and silver ammonia solution is 1:0.01-1. The reduction reaction is carried out at a temperature of 20-60℃ for 1-3 hours.

6. The method for preparing antibacterial flake-shaped silver-coated copper powder according to any one of claims 1-3, characterized in that, In step S3, the aluminum source precursor is at least one of aluminum acetylacetonate, triethylaluminum, or triisobutylaluminum; The temperature of the vapor phase chemical deposition reaction is 200-250℃, and the time is 0.5-2h.

7. The method for preparing antibacterial flake-shaped silver-coated copper powder according to any one of claims 1-3, characterized in that, The method also includes step S4, in which an aminosilane coupling agent solution is added to the sheet-like silver-coated copper powder with an alumina coating to carry out a hydrolysis reaction, and then an aldehyde-based polyethylene glycol is added to carry out an addition reaction to obtain hydrophilic modified sheet-like silver-coated copper powder.

8. The method for preparing antibacterial flake-shaped silver-coated copper powder according to claim 7, characterized in that, The aminosilane coupling agent is at least one of 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-aminoethyl-3-aminopropyltrimethoxysilane or N-aminoethyl-3-aminopropyltriethoxysilane. The mass ratio of the sheet-like silver-coated copper powder with an alumina coating, the aminosilane coupling agent, and the aldehyde-based polyethylene glycol is 1:0.01-0.1:0.05-0.

2.

9. An antibacterial flake-shaped silver-coated copper powder, characterized in that, It is prepared by the preparation method described in any one of claims 1-8.

10. An antibacterial fabric, characterized in that, It includes a cotton fabric and the antibacterial flake-shaped silver-coated copper powder of claim 9 loaded on the surface of the cotton fabric.

Citation Information

Patent Citations

  • Corrosion-resistant flaky silver-coated copper powder, preparation method thereof and electromagnetic shielding shell

    CN119927207A

  • Method for fabricating Ag-coated Cu powder

    KR102271692B1